Thyroid Dysfunction, Vitamin B12, and Folic Acid Deficiencies Are Not Associated With Cognitive Impairment in Older Adults in Lima, Peru - Monica M. Diaz (Frontiers in Public Health, 2021)
Background: Reversible etiologies of cognitive impairment are common and treatable, yet the majority of mild cognitive impairment (MCI) and dementia research in Latin America has focused on irreversible, neurodegenerative etiologies.Objective: We sought to determine if thyroid dysfunction and vitamin B12 and folate deficiencies are associated with cognitive disorders among older adults with memory complaints in Lima, Peru.Methods: This was a retrospective review of patients who presented for cognitive evaluations to a multidisciplinary neurology clinic in Lima, Peru from January 2014 to February 2020. We included individuals aged ≥60 years, native Spanish-speakers, with at least a primary school educational level and a complete clinical assessment. Patients had either subjective cognitive decline (SCD), MCI, or dementia. One-way ANOVA and multiple logistic regression analyses were performed.Results: We included 720 patients (330 SCD, 154 MCI, and 236 dementia); the dementia group was significantly older [mean age SCD 69.7 ± 4.1, dementia 72.4 ± 3.7 (p = 0.000)] and had lower folate levels than SCD patients. The MCI group had higher free T3 levels compared with SCD patients. Those with lower TSH had greater dementia risk (OR = 2.91, 95%CI: 1.15–6.86) but not MCI risk in unadjusted models. B12 deficiency or borderline B12 deficiency was present in 34% of the dementia group, yet no clear correlation was seen between neuropsychological test results and B12 levels in our study. There was no association between MCI or dementia and thyroid hormone, B12 nor folate levels in adjusted models.Conclusion: Our findings do not support an association between metabolic and endocrine disorders and cognitive impairment in older Peruvians from Lima despite a high prevalence of B12 deficiency. Future work may determine if cognitive decline is associated with metabolic or endocrine changes in Latin America.